2011
DOI: 10.1177/1934578x1100601032
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antioxidant Activities of Leaf and Root Volatile Oils of Morinda lucida

Abstract: Morinda lucida (L.) Benth. (Rubiacae) is used in traditional medicine in many West African countries for the treatment of various human diseases. The leaves and roots of this plant were subjected to hydro-distillation to obtain volatile oils which were analyzed by high resolution GC/MS. Fifty compounds were identified in the leaf volatile oil and the major compounds were α-terpinene (17.8%) and β-bisabolene (16.3%). In the root oil, 18 compounds were identified, the major constituents being 3-fluoro-p-anidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…The leaves were sufficiently air-dried in 5 days at the ambient room temperature, while the stem was cut into smaller pieces and air-dried in 7 days. They were pulverized and essential oil was extracted for 3 h from each (200 g) using modified Clevenger-type apparatus [25]. The hydrodistillation experiment was carried out twice for the leaf and stem separately to obtain enough oil for bioactivity assays.…”
Section: Methodsmentioning
confidence: 99%
“…The leaves were sufficiently air-dried in 5 days at the ambient room temperature, while the stem was cut into smaller pieces and air-dried in 7 days. They were pulverized and essential oil was extracted for 3 h from each (200 g) using modified Clevenger-type apparatus [25]. The hydrodistillation experiment was carried out twice for the leaf and stem separately to obtain enough oil for bioactivity assays.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH assay of the essential oil was carried out as previously described [ 22 ]. A solution of 0.135 Mm DPPH in methanol was prepared and 1.0 mL of this solution was mixed with 1.0 mL of the essential oil prepared in methanol containing 0.025–0.50 mg/mL of the oil and commercial antioxidants (vitamin C and rutin).…”
Section: Methodsmentioning
confidence: 99%
“…Okoh et al [38] identified 50 compounds where α -terpinene was the major constituent with 17.8%, while in this study it represented only 0.8%. This difference could be attributed to the number of compounds identified in each study, since in this study, 63 components were identified, representing 95.4% of the total oil content.…”
Section: Discussionmentioning
confidence: 50%